Colonic and systemic effects of extruded whole-grain sorghum consumption in growing Wistar rats - Llopart, Emilce Elina (2017)
Colonic effects of extruded whole-grain sorghum diets were evaluated using a model of growing rats. In all, twenty-four male Wistar rats were fed control (C), extruded white sorghum (EWS) or red sorghum (ERS). Consumption of sorghum diets showed satiety properties, with reduction of caecal pH, and lower activity of β-glucosidase and β-glucuronidase enzymes. Decreased copper zinc superoxide dismutase and manganese superoxide dismutase and increased catalase and glutathione peroxidase levels were observed in colonic mucosa. The induction of antioxidant enzymes occurred through the activation of the nuclear factor erythroid 2-related factor 2 protein and its subsequent translocation into the nucleus. ERS was able to decrease the proliferation of proximal mucosa of colon, demonstrating a possible effect against colorectal tumourigenesis. EWS increased proliferation and also apoptosis, ensuring the re-establishment of homoeostasis of the colonic mucosa. No antioxidant systemic effect (serum or hepatic level) was observed. It is likely that despite the extrusion the low bioavailability of the phenolic compounds of sorghum diets caused them to exert mainly acute effects at the colon level. Extruded whole-grain sorghum is a good functional ingredient that might be promising in dietary prevention of intestinal diseases.